1989
DOI: 10.1111/j.1398-9995.1989.tb04174.x
|View full text |Cite
|
Sign up to set email alerts
|

Blocking activity of mite‐specific IgG antibodies studied by skin tests

Abstract: The aim of the study was to determine whether IgG antibodies from patients on specific immunotherapy could inhibit skin test reactivity of allergens when mixed with them prior to testing. In a preliminary double-blind study, mite extracts were incubated with glycero-saline solution or non-specific IgG and used in testing 15 patients. Wheal and flare diameters produced with the two mite extracts did not differ significantly. In a second double-blind study with 15 other patients, skin tests using mite extracts i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Lichtenstein et al [8] showed in 1968 that SIT-induced IgG blocked basophil histamine release; this observation has subsequently been confirmed by many other investigators [9][10][11]. Furthermore, SIT-induced IgG blocks passive cutaneous anaphylaxis and serum-IgE facilitated antigen presentation to T cells [7,[12][13][14][15]. It has been hypothesized that 'blocking' antibodies represent an important aspect of the mechanism of SIT [16,17].…”
Section: Introductionmentioning
confidence: 96%
“…Lichtenstein et al [8] showed in 1968 that SIT-induced IgG blocked basophil histamine release; this observation has subsequently been confirmed by many other investigators [9][10][11]. Furthermore, SIT-induced IgG blocks passive cutaneous anaphylaxis and serum-IgE facilitated antigen presentation to T cells [7,[12][13][14][15]. It has been hypothesized that 'blocking' antibodies represent an important aspect of the mechanism of SIT [16,17].…”
Section: Introductionmentioning
confidence: 96%
“…Already before 1940 it was shown that in sera of patients that had received a course of allergen-specific im munotherapy a heat-stable antibody had developed [1,2], This antibody was called blocking antibody because of its allergen-neutralizing capacity in skin tests [3][4][5]. Allergen extracts preincubated with serum o f desensitized patients showed significantly decreased diameters of wheals and flares in the skin test compared to allergen extracts incubat ed with scrum of the same individuals before immunothera py or with saline.…”
Section: Introductionmentioning
confidence: 99%
“…verabreicht, bis ein merklicher Schutz erreicht wird, der sich durch verringerte Allergiesymptomatik äußert ("Desensibilisierung"). Die wiederholte Applikation des Allergens führt erwiesenermaßen zur Induktion von IgG-Antikör-pern, die das Zeichen für eine gelungene spezifische Immuntherapie darstellen [2,40,41]. Paradoxerweise sind die Allergenextrakte zusätzlich mit Aluminiumhydroxid versetzt, einem Adjuvans, von dem man weiß, das es die Th2-Antwort bei Immunisierungen fördert -und damit auch die Induktion von IgE [42][43][44].…”
Section: Klassische Immuntherapie -Konzept Der Blockierenden Antikörperunclassified